The Annapurna Water Cooperation Consensus (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available.DOI: http://dx.doi.org/10.3126/hn.v15i0.11382HYDRO Nepal JournalJournal of Water, Energy and EnvironmentVolume: 15, 32014, JulyPage: 90-92